Limits on the Low-energy Electron Antineutrino Flux from the Brightest Gamma-Ray Burst of All Time - S. Abe; T. Araki; S. Chauhan; K. Chiba; T. Eda; M. Eizuka; Y. Funahashi; A. Furuto; A. Gando; Y. Gando; S. Goto; T. Hachiya; et al. (The Astrophysical Journal)
The electron antineutrino flux limits are presented for the brightest gamma-ray burst (GRB) of all time, GRB221009A, over a range of 1.8–200 MeV using the Kamioka Liquid Scintillator Antineutrino Detector. Using multiple time windows ranging from minutes to days surrounding the event to search for electron antineutrinos coincident with the GRB, we set an upper limit on the flux under the assumption of several power-law neutrino source spectra, with power-law indices ranging from 1.5 to 3 in steps of 0.5. No excess was observed in any time windows ranging from seconds to days around the event trigger time T _0 . For a power-law index of 2 and a time window of T _0  ±  500 s, a flux upper limit of 2.34  ×  10 ^9 cm ^−2 was calculated. The limits are compared to the results presented by IceCube.